Japan-specific viewpoints for bridging city planning and the industry of agriculture - Noriko Ashiya (Philipps-University Marburg, School of Business and Economics, 2023)
Japan has experience reviving its real estate market through the introduction of securitization, and this could work for farmland even though farmland in Japan operates under different property regulations than office buildings and residences. However, farmland usage and its activation would have broad impacts on city planning and extend to trade issues, so in this international friendship meeting, I would like to introduce the following ideas and to try to incorporate our different cultural viewpoints. (1) Michael E. Porter's (1990) insights on The Netherlands' agriculture are still pertinent today, and appear as though they may be effective in the activation of Japanese agriculture, even 30 years since his publication. (2) However, Japan's attempt to replicate the Netherlands' success within the last 10 years has brought no change to the 30-year decline of the agricultural industry. The practice needs modifications. (3) A prominent candidate city in Japan for this modified practice, possessing many characteristics of The Netherland's famous Food Valley, is Miura city, 100 km south of Tokyo.
Keywords: Q15; K12; R14; 330